FAKTOR-FAKTOR YANG MEMPENGARUHI KELENGKAPAN PENGUNGKAPAN DALAM LAPORAN TAHUNAN PADAPERUSAHAAN PERDAGANGAN PERIODE 2012-2014 DI BURSA EFEK INDONESIA - Yulia Istia Ningsih (Ekonomis: Journal of Economics and Business, 2018)
This research aims to know the factors that affect the completeness of the disclosure in the annual report on trading company registered in BEI 2012-2014 year. The selection of the sample using a purposive sampling. Based on the criteria of the 45 companies that become the population, retrieved 15 companies that are being sampled in this study. The independent variable in this study is the liquidity, leverage, net profit margin, the company's size and age of the company. While the dependent variable is represented by the level of disclosure of information in the annual report with the awarding of the score over the disclosure items that are listed in the annual report. The results of this research show that partially during the period of 2012-2014 for the size of the company's positive effect towards completeness of disclosure in the annual report. As for liquidity, leverage, net profit margin, and the age of the company does not affect the completeness of the disclosure in the annual report. Simultaneously influence among variables showed a non towards completeness of disclosure in the annual report.Keywords: Disclosure annual report, liquidity, Leverage, Net Profit Margin, the company's Size, age of the company